Low voltage ride-through enhancement of wind turbine generators - Chong, Xian Sheng. (2011)
Firstly, literature review is done on the operating principle of doubly fed induction generator (DFIG). Then the issues on power quality are discussed where voltage dip is chosen to be the fault for experiment use. After which the voltage generated by series compensator is analyzed. After successfully setting up a DFIG emulator, experiments are conducted on standalone DFIG system, grid-connected DFIG system and injection of linear ramp voltage respectively. Standalone experiment is done to investigate how rotor side converter (RSC) will affect the stability of induction generator output power. A stable output power generated by induction generator has to be guaranteed before moving on the next experiment.